2023
DOI: 10.1093/gbe/evad025
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure, Demographic History, and Adaptation of Giant Honeybees in China Revealed by Population Genomic Data

Abstract: There have been many population-based genomic studies on human-managed honeybees (Apis mellifera and Apis cerana), but there has been a notable lack of analysis with regard to wild honeybees, particularly in relation to their evolutionary history. Nevertheless, giant honeybees have found to occupy distinct habitats and display have remarkable characteristics, which are attracting an increase amount of attention. In this study, we de novo sequenced and then assembled the draft genome sequence of the Himalayan g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
(111 reference statements)
0
3
0
Order By: Relevance
“…Further to the east, Huang et al (2022) reported on specimens housed in the National Zoological Museum of China collected in the upper regions the Brahmaputra River: one along the Yarlung Zangbo River (in Motuozhen, Medog County), and another near Bomé along the Palong Zhangbo River, a tributary to the Yarlung Zhangbo, both in Nyingche Prefecture, Xizang. Cao et al (2023) analyzed specimens collected in the nearby watershed of the Palong Zhangbo River. In Yunnan, Yang et al (2015) reported the species from Deqin County (Shengpingzhen), near the Lancang River (upper Mekong River; included in Huang et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further to the east, Huang et al (2022) reported on specimens housed in the National Zoological Museum of China collected in the upper regions the Brahmaputra River: one along the Yarlung Zangbo River (in Motuozhen, Medog County), and another near Bomé along the Palong Zhangbo River, a tributary to the Yarlung Zhangbo, both in Nyingche Prefecture, Xizang. Cao et al (2023) analyzed specimens collected in the nearby watershed of the Palong Zhangbo River. In Yunnan, Yang et al (2015) reported the species from Deqin County (Shengpingzhen), near the Lancang River (upper Mekong River; included in Huang et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Two nearly 50-year-old specimens in the National Zoological Museum of China were also collected in this same region. Cao et al (2023) collected samples from several villages in Rikaze, Xizang, in the watershed of Phung Chu (the upper reaches of the Arun River) that extends northward from eastern Nepal. Further to the east, Huang et al (2022) reported on specimens housed in the National Zoological Museum of China collected in the upper regions the Brahmaputra River: one along the Yarlung Zangbo River (in Motuozhen, Medog County), and another near Bomé along the Palong Zhangbo River, a tributary to the Yarlung Zhangbo, both in Nyingche Prefecture, Xizang.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation